PERANAN HAJI MISBACH DALAM PERGERAKAN ISLAM KOMUNISME DI SURAKARTA PADA TAHUN 1914-1926 - andriani, beky frisca (KARMAWIBANGGA: Historical Studies Journal, 2020)
This study aims to: (1) describe the biography of Haji Misbach; (2) describe Haji Misbach's thoughts about the Islamic communism movement; (3) to describe the role of Haji Misbach in the Islamic communism movement in Surakarta in 1914- 1926. The research method used in this research is a historical method written descriptively-analytically. By using historical, political, social and religious approaches. The first stage is heuristics. Second, verification. Third, interpretation. Fourth, historiography, with the nature of research, literature or literature studies. The results of this study indicate that: (1) Haji Misbach was born with the name Ahmad, in Kauman, Surakarta, in 1876. He grew up in a family of batik traders. He is better known as Haji Misbach; (2) Haji Misbach wanted to juxtapose the teachings of communism and Islam. In his thought, Haji Misbach called on Muslims to fight and jihad against the capitalists and Dutch colonialism. On the one hand, Communism is a means of struggle against capitalism; (3) The role of Haji Misbach in the Islamic communism movement occurred during 1914 to 1926. He fought a lot by joining in several organizations and was active in establishing,Â leading, and managing a newspaper which he used as a media to carry out propaganda fighting for people's freedom from shackles. Capitalism wrapped in colonialism.